2014
DOI: 10.1111/pce.12461
|View full text |Cite
|
Sign up to set email alerts
|

Excising stem samples underwater at native tension does not induce xylem cavitation

Abstract: Xylem resistance to water stress-induced cavitation is an important trait that is associated with drought tolerance of plants. The level of xylem cavitation experienced by a plant is often assessed as the percentage loss in conductivity (PLC) at different water potentials. Such measurements are constructed with samples that are excised underwater at native tensions. However, a recent study concluded that cutting conduits under significant tension induced cavitation, even when samples were held underwater durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
80
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(83 citation statements)
references
References 45 publications
(126 reference statements)
1
80
1
1
Order By: Relevance
“…This method, however, is performed with the implicit assumption that no novel refilling (to our knowledge) is occurring. Nevertheless, more recent data indicate that the rehydration procedure may facilitate vessel refilling (Trifilò et al, 2014;Venturas et al, 2015). Venturas et al (2015) concluded that differences in hydraulic conductivity were mainly caused by a refilling artifact as opposed to a cutting-artifact.…”
Section: Implications For Hydraulic Measurementsmentioning
confidence: 99%
See 2 more Smart Citations
“…This method, however, is performed with the implicit assumption that no novel refilling (to our knowledge) is occurring. Nevertheless, more recent data indicate that the rehydration procedure may facilitate vessel refilling (Trifilò et al, 2014;Venturas et al, 2015). Venturas et al (2015) concluded that differences in hydraulic conductivity were mainly caused by a refilling artifact as opposed to a cutting-artifact.…”
Section: Implications For Hydraulic Measurementsmentioning
confidence: 99%
“…Nevertheless, more recent data indicate that the rehydration procedure may facilitate vessel refilling (Trifilò et al, 2014;Venturas et al, 2015). Venturas et al (2015) concluded that differences in hydraulic conductivity were mainly caused by a refilling artifact as opposed to a cutting-artifact. Here, the experimental design effectively simulated the methods many labs currently use for the preparation/maintenance of samples in xylem hydraulic conductivity measurements.…”
Section: Implications For Hydraulic Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we note that the long-vessel artefact has been rebutted by other studies Hacke et al 2014), and this issue remains unresolved. (2) To avoid artefactual embolism induction caused by the cutting of a branch, while the xylem is under tension, rehydration/relaxation of samples has been suggested, followed by re-cutting under degassed water (Wheeler et al 2013), although this artefact has not been found by others (Venturas et al 2015). Alternatively, the relaxation procedure has been shown to introduce other potential errors related to rehydration-induced embolism refilling (Trifilo`et al 2014b).…”
Section: Methodological Precautionsmentioning
confidence: 99%
“…Whereas Scoffoni and Sack (2014) showed that the artifact described by Wheeler et al (2013) has no impact on leaf xylem hydraulic conductance, there is some uncertainty about its importance in stems or shoots (Trifilò et al, 2014;Venturas et al, 2014). The results of Wheeler et al (2013) indicate that more embolism could be induced by cutting samples that are under midrange xylem tension (e.g.…”
mentioning
confidence: 95%